Analysis of Short Story Reading Skills and Writing Skills of Elementary School Students: Analisis Keterampilan Membaca Cerpen dan Keterampilan Menulis Siswa Sekolah Dasar - Yulinta, Rosania; Sukartiningsih, Wahyu; Indarti, Titik (Madrosatuna: Journal of Islamic Elementary School, 2024)
Merdeka-Learning is an educational process to create interesting and creative learning situations.The study aims to determine the ability of short story reading skills and writing skills of students in elementary school.Merdeka Learning means learning, thinking, philosophizing and seeking information.Competence that comes from interesting learning allows a process when teachers and students experience real learning as well as experience the results. This results in smart, strong-minded, experienced and critical thinking learners, which reflects the goals of Indonesian national language and literature education. In Indonesian language and literature education, the concept of independent learning aims to increase students' interest and potential in character building, knowledge acquisition and critical thinking to analyze a problem through fun learning. In this research, the technique used is a qualitative-based data collection technique. The collection of this observation is a type of library research by collecting information about Indonesian literary works in the form of journals, books, articles and other research works. According to the data collected, it displays that students can think more sharply when implementing an independent learning curriculum because the learning process creates an innovative and creative atmosphere. Students learn according to their abilities and possibilities and are more independent in learning. The results of this study are Based on the results of data analysis above relevant: literacy There is a positive or significant relationship with writing skills.